Phenotypic and Genomic Properties of a Novel Deep-Lineage Haloalkaliphilic Member of the Phylum Balneolaeota From Soda Lakes Possessing Na+-Translocating Proteorhodopsin - Sorokin, Dimitry Y.; Muntyan, Maria S.; Toshchakov, Stepan V.; Korzhenkov, Aleksei; Kublanov, Ilya V. (Frontiers in Microbiology, 2018)
Stable development of a heterotrophic bacterial satellite with a peculiar cell morphology has been observed in several enrichment cultures of haloalkaliphilic benthic filamentous cyanobacteria from a hypersaline soda lake in Kulunda Steppe (Altai, Russia). The organism was isolated in pure culture (strain Omega) using sonicated cyanobacterial cells as substrate and it was identified as a deep phylogenetic lineage within the recently proposed phylum Balneolaeota. It is an obligately aerobic heterotroph utilizing proteins and peptides for growth. The cell morphology significantly varied from semicircles to long filaments depending on the growth conditions. The cultures are red-orange colored due to a presence of carotenoids. The isolate is an obligate alkaliphile with a pH range for growth from 8.5 to 10.5 (optimum at 9.5-10) and moderately salt-tolerant with a range from 0.3 to 3 M total Na+ (optimum at 1 M). The genome analysis of strain Omega demonstrated a presence of gene, encoding a proteorhodopsin forming a separate branch in the sodium-translocating proteorhodopsin family. Experiments with washed cells of Omega confirmed light-dependent sodium export. A possible physiological role of the sodium proteorhodopsin in strain Omega is discussed. Phylogenomic analysis demostrated that strain Omega forms an deep, independent branch of a new genus and family level within a recently established phylum Balneolaeota.